2019
DOI: 10.15282/ijame.16.3.2019.21.0533
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency Ratio (EER) of Novel Air Conditioning System on LPG Fuelled Vehicle: A Lab-Scale Investigation

Abstract: Alternative fuels have become an effective solution to reduce the impact of road transport on the environment. On the other hand, the growing uses of air-conditioning (AC) have contributed to worsening the fuel economy of passenger vehicles. Liquid petroleum gas (LPG), if injected in the gaseous phase to power SI engines, may allow reducing the fuel consumption due to AC devices through the recovery of cooling energy from the fuel systems. This paper presents lab-scale tests of an air conditioning system proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…They reported that R600a with nanolubricant worked safely and energy consumption for 0.5g/L TiO2 -R600a refrigerant was lessened by 9.6% compared to pure R600a. A detailed review to determine the possibility of using nano refrigerant and nano lubricant in a vapour compression system was reported in [38][39][40] Also, a few articles addressed the exergetic performance evaluation of AC which is an important attribute for an energy-efficient system design. Considering this purpose, in this work, the energetic and exergetic performance of a split type air conditioner containing TiO2 nanoparticles/mineral oil lubricant mixture and blend of R22/R600a (60:40 by mass charged as refrigerant) was examined to extend the current frontier of knowledge and to minimise the research gap.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that R600a with nanolubricant worked safely and energy consumption for 0.5g/L TiO2 -R600a refrigerant was lessened by 9.6% compared to pure R600a. A detailed review to determine the possibility of using nano refrigerant and nano lubricant in a vapour compression system was reported in [38][39][40] Also, a few articles addressed the exergetic performance evaluation of AC which is an important attribute for an energy-efficient system design. Considering this purpose, in this work, the energetic and exergetic performance of a split type air conditioner containing TiO2 nanoparticles/mineral oil lubricant mixture and blend of R22/R600a (60:40 by mass charged as refrigerant) was examined to extend the current frontier of knowledge and to minimise the research gap.…”
Section: Introductionmentioning
confidence: 99%